Effect of adenine, sucrose and plant growth regulators on the indirect organogenesis and on in vitro flowering in Begonia x hiemalis fotsch - Awal, A.; Ahmed, A.B.A.; Taha, R.M.; Yaacob, J.S.; Mohajer, S. (2013)
Efficient shoot bud formation (94.5 Â± 7.59), in vitro regeneration and production of flowers were obtained from sterile plants of Begonia x hiemalis Fotsch. An in vitro regeneration was attempted using immature reproductive organs, which were not commonly used before, such as young inflorescences, peduncles and petals of flowers collected in the field. The flower segments were cultured on solid Murashige and Skoog (MS) medium, supplemented with various concentrations and combinations of plant growth regulators (PGRs) and adenine. Within 8 weeks of the culture period, the highest frequency of reproductive shoot regeneration (red calyx, 8.50) was obtained from explants of immature inflorescence cultured on the MS medium supplemented with 1.0 mgL-1 benzyl amino purine (BA) and 1.0 mgL-1 1-naphthalene acetic acid (NAA), added with 40 mgL-1 adenine and 3 sucrose. To attain further root growth and maturity, the clonal plantlets (with or without reproductive shoots) were excised and sub-cultured onto the MS medium fortified with 1.0 mgL-1 Gibberellic acid (GA3). 87 of the regenerated plantlets were successfully acclimatized on 2:1:1 ratio of peat: soil: sand, under greenhouse conditions. All of them were capable of producing true-to-type flowers. The in vitro developed reproductive shoots, also further generated complete, small flowers, which were morphologically similar to the in vivo types, following an ex vitro acclimatization.This study provides an alternative approach to generate early flowering in Begonia without undergoing the full growth cycle and hence can help overcome problems associated with flower growth and development in this species. The present study revealed that floral parts (inflorescence, peduncle and petals) could also be used as a source of explants besides the commonly used tissues such as leaf, stem, shoot and root segments.